2019
DOI: 10.1101/810093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defective Nucleotide Catabolism Defines a Subset of Cancers Sensitive to Purine Nucleoside Phosphorylase Inhibition

Abstract: 2 Small molecule inhibitors of purine nucleoside phosphorylase (PNP) have been explored as a treatment strategy for leukemia and lymphoma, however, the determinants of response to this class of drugs are incompletely understood. PNP inhibitors impair cell proliferation by preventing catabolism of the nucleoside deoxyguanosine (dG) which induces toxic imbalances amongst intracellular deoxyribonucleotide triphosphate (dNTP) pools following its phosphorylation and trapping by nucleoside kinases. We hypothesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Recent work has shown that the dNTP-degrading enzyme SAMHD1 protects against cytotoxic dGTP buildup upon deoxyguanosine supplementation. SAMHD1-deficient tumor cells are sensitive to dGTP accumulation caused by deoxyguanosine supplementation and purine nucleoside phosphorylase (PNP) inhibition 46,47 . Nucleotide imbalance is also implicated in non-cancer human disease settings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that the dNTP-degrading enzyme SAMHD1 protects against cytotoxic dGTP buildup upon deoxyguanosine supplementation. SAMHD1-deficient tumor cells are sensitive to dGTP accumulation caused by deoxyguanosine supplementation and purine nucleoside phosphorylase (PNP) inhibition 46,47 . Nucleotide imbalance is also implicated in non-cancer human disease settings.…”
Section: Discussionmentioning
confidence: 99%
“…[ 154 ]). Notably, SAMHD1 has also been reported to protect cells from build‐up of cytotoxic dGTP, which could be exploited to target SAMHD1‐deficient cancer cells with PNP inhibitors [ 155 , 156 ]. Thus, there is a striking parallel in the role of SAMHD1 in protecting cells from excess dGTP and the triphosphate metabolite of nelarabine (ara‐GTP).…”
Section: Samhd1mentioning
confidence: 99%
“…Thus, there is a striking parallel in the role of SAMHD1 in protecting cells from excess dGTP and the triphosphate metabolite of nelarabine (ara‐GTP). Given the apparent lack of SAMHD1 expression in T‐cell malignancy cell lines [ 151 , 156 ], it is tempting to speculate that SAMHD1 (or rather lack of) is responsible for the original observations of dG and ara‐G selective T‐cell toxicity together with subsequent experiments, which formed the basis of nelarabine being developed as a T‐cell‐specific drug. Another interesting point is that many of the triphosphate metabolites of these nucleoside analogues can also allosterically activate SAMHD1 at the AS2 site [ 14 , 143 , 144 , 145 , 148 , 149 ], but the biological relevance in cancer cells, if any, has been little explored/observed, perhaps owing to basal dNTPs already being sufficient for tetramerisation, which is known to be long‐lived [ 104 ].…”
Section: Samhd1mentioning
confidence: 99%
“…T-Cell-targeted antiproliferative properties of PNPIs open various therapeutic uses in the treatment of autoimmune diseases (e.g., inflammatory bowel disorders, multiple sclerosis, rheumatoid arthitis, psoriasis, and organ transplant rejection) and T-cell malignancies (leukemias and lymphomas) . Recent research shed light on specific mutations responsible for sensitivity of cells to PNP inhibition. , Such genetic markers potentially open other opportunities in more targeted therapies and even in a treatment of solid tumors. Moreover, it has been demonstrated that accumulation of guanosine (Guo) by PNPIs activates various toll-like receptors (TLRs), which, paradoxically, leads to immune activation effects.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Recent research shed light on specific mutations responsible for sensitivity of cells to PNP inhibition. 13 , 14 Such genetic markers potentially open other opportunities in more targeted therapies and even in a treatment of solid tumors. Moreover, it has been demonstrated that accumulation of guanosine (Guo) by PNPIs activates various toll-like receptors (TLRs), which, paradoxically, leads to immune activation effects.…”
Section: Introductionmentioning
confidence: 99%